Designing large-scale antenna array using sub-array - Naimul Mukit; Md. Rafiqul Islam; Mohamed Hadi Habaebi; A. H. M. Zahirul Alam; Khaizuran Abdullah; Norun Farihah Abdul Malek; Rauful Nibir; Noor Hidayah M. Adnan; Eid Osman (Bulletin of Electrical Engineering and Informatics, 2019)
Antenna array of large scale have been examined for different applications including 5G technology. To get better data rate or a reliable link substantial number of antenna arrays have been utilized to provide high multiplexing gains as well as array gains with high directivity. In this paper a simple but efficient implementation technique of using sub-arrays for the improvement of large-sized uniform arrays. By repeating a small sub-array multiple times large arrays can be designed. This implication of utilizing small array simplifies the design of a larger array which allows the designer to concentrate on the smaller sub-array before assembling larger arrays. So, by investigating the sub arrays the performance and radiation characteristics of large arrays can be anticipated. The array-factor for a planar sub-array of 2x2 (4 elements) is analyzed using Mat-lab software and then a large array is formed by placing the 2x2 sub-array indifferent configurations in a rectangular arrangements up to 8x8 planar array. And then the results are validated with CST (Computer simulation technology) simulation results.In this way the array-factors, directivities, HPBWs, and side lobes of the constructed large arrays are analyzed and associated with the small sub-array.